Semantic technologies in electronic government: Tutorial and workshop - Harris, S; Gibbons, J; Davies, J; Tsui, A; Crichton, C (2008)
Joined-up government depends fundamentally on semantics - on the computable representation of meaning, so that data is associated with appropriate metadata from the start, and this association is maintained as the data is manipulated. This paper summaries a tutorial and workshop on semantic technologies for supporting electronic government. Copyright 2008 ACM.